Supply Chain Management Pabrik Roti ABC Dengan Metode Weighted Moving Average (WMA) - Fransiska Prihatini Sihotang (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2020)
ABC Bread Factory is a company engaged in the production of bread. In carrying out its business processes the company has difficulty in determining the production amount, does not record sales turnover, reports on purchases of raw materials and sales, and there is no recording of the distribution of bread produced, For this reason it is necessary to design a supply chain management information system that will provide control over the stock of raw materials and production results and produce reports needed by the company. The development process uses the Rational Unified Process method. In the initial stage for analysis of problems using PIECES, then for needs analysis using the Usecase Diagram. At the planning stage Class Diagrams, Activity Diagrams and Sequence Diagrams are used. Development of the system uses Php and Mysql for its database. The supply chain management information system is expected to be able to help in overcoming problems that occur in ABC Bakeries in carrying out its operational activities.